2015
DOI: 10.1105/tpc.15.00105
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dihydrolipoyl Dehydrogenase Activity Shapes Photosynthesis and Photorespiration of Arabidopsis thaliana

Abstract: Mitochondrial dihydrolipoyl dehydrogenase (mtLPD; L-protein) is an integral component of several multienzyme systems involved in the tricarboxylic acid (TCA) cycle, photorespiration, and the degradation of branched-chain a-ketoacids. The majority of the mtLPD present in photosynthesizing tissue is used for glycine decarboxylase (GDC), necessary for the high-flux photorespiratory glycine-into-serine conversion. We previously suggested that GDC activity could be a signal in a regulatory network that adjusts carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 86 publications
1
97
0
Order By: Relevance
“…As one of the most abundant mitochondrial proteins, this enzyme has for many decades been the subject of detailed study (Douce et al ). Arabidopsis knockouts of the L‐protein, a mitochondrial dihydrolipoyl dehydrogenase that mainly participates in the glycine decarboxylase complex, revealed that they were characterized by reduced levels of TCA cycle and photorespiratory intermediates, yet they had enhanced rates of photosynthesis and growth (Timm et al ). Collectively, these examples underscore the importance of mitochondrial reactions in proper chloroplast, and hence cellular function, and highlight that the manipulation of certain steps of the pathway can result in enhanced aerial growth, and indeed, crop yield.…”
Section: Role Of the Tca Cycle In Photosynthetic Tissuesmentioning
confidence: 99%
“…As one of the most abundant mitochondrial proteins, this enzyme has for many decades been the subject of detailed study (Douce et al ). Arabidopsis knockouts of the L‐protein, a mitochondrial dihydrolipoyl dehydrogenase that mainly participates in the glycine decarboxylase complex, revealed that they were characterized by reduced levels of TCA cycle and photorespiratory intermediates, yet they had enhanced rates of photosynthesis and growth (Timm et al ). Collectively, these examples underscore the importance of mitochondrial reactions in proper chloroplast, and hence cellular function, and highlight that the manipulation of certain steps of the pathway can result in enhanced aerial growth, and indeed, crop yield.…”
Section: Role Of the Tca Cycle In Photosynthetic Tissuesmentioning
confidence: 99%
“…Furthermore, plants under SSL conditions exhibited the up-regulation of glutamate-ammonia ligase (also recognized as glutamine synthetase, GS), an enzyme that assimilates the ammonia generated in the GCC via the GS/GOGAT cycle by consuming reducing equivalents from ferrodoxin and/or NADPH/ATP. In turn, up-regulation of mtLPD, HPR, and GCC activity suggest that the plants under SSL conditions were regulating the photorespiratory carbon cycle, effectively shaping photosynthesis (Timm et al, 2015). This allows for increased performance of the C3 cycle and enhance the generation of ribulose-1,5-bisphosphate (RuBP), also facilitating the consumption of photorespiratory metabolites and, in turn, photosynthetic carbon assimilation (Voss et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in C c also accelerates the production of photorespiratory intermediates, e.g., glycine and glycerate, which inhibit the Calvin-Benson cycle (Chastain and Ogren, 1989; Eisenhut et al, 2007; Timm et al, 2012, 2015). In Arabidopsis thaliana plants with elevated glycine decarboxylase activity, the rapid acceleration of the photorespiratory pathway lowers the accumulation of photorespiratory metabolites including those which impair Rubisco activation and possibly the activity of other enzymes of the Calvin-Benson cycle, increasing the performance of the Calvin-Benson cycle (Timm et al, 2012, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis thaliana plants with elevated glycine decarboxylase activity, the rapid acceleration of the photorespiratory pathway lowers the accumulation of photorespiratory metabolites including those which impair Rubisco activation and possibly the activity of other enzymes of the Calvin-Benson cycle, increasing the performance of the Calvin-Benson cycle (Timm et al, 2012, 2015). Furthermore, N. tabacum plants grown under high light and high nitrogen concentration up-regulate photorespiratory pathway to maintain high rates of photosynthesis (Huang et al, 2014, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation